Blood Glucose Level in Low Birth Weight Babies in First 48 Hours of Life - Khairuzzaman, Md; Sarker, Nihar Ranjan; Sarker, Mst Monjuman Ara; Matin, Abdul; Rakshit, Sudesh Chandra; Mojumder, Bikash; Absar, Md Nurul (Journal of Current and Advance Medical Research, 2018)
Background: Transient hypoglycemia in the early neonatal period is a common adaptive phenomenon as the newborn changes from the fetal state of continuous transplacental glucose consumption to intermittent nutrient supply following cessation of maternal nutrition at birth. This adaptation is well established in term appropriate for gestational age babies but is not established in low birth weight babies. Objective: this study was undertaken to evaluate glycemic status of the low birth weight babies and impact of early feeding. Methodology: This prospective observational study was done in the department of Pediatrics and department of obstetrics, Rangpur Medical College Hospital, Rangpur, Bangladesh from September 2005 to February 2006 for a period of six (6) months. Blood sugar was estimated at birth (cord blood) and then from capillary blood at 2 hours, 4 hours, in between 12 to 24 hours and in between 24 to 48 hours. The capillary blood was obtained by heel prick. Venous sample was sent to the college laboratory for confirmation if the blood sugar was less than 2.6 mmol/L (47 mg/dL). Result: In the first 48 hours, the blood glucose levels were lowest at 2 hours after delivery and the level gradually increased with increasing postnatal age in low birth weight babies. Birth weight had a positive correlation with blood glucose levels of low birth weight babies. The overall incidence of hypoglycemia in low birth weight babies were 31.8%, among them 77.1% asymptomatic and 22.9% symptomatic. The mean blood glucose levels were significantly high in early feed group than the delayed feed group babies (p<0.05). Conclusion: The blood glucose levels is lowest at 2 hours after delivery and the level gradually increases with increasing postnatal age in low birth weight babies which is a positive correlation with blood glucose levels of low birth weight babies. Journal of Current and Advance Medical Research 2018;5(1):33-38